The CCAAT/Enhancer-Binding Protein beta - SerpinB3 axis inhibition as a novel strategy for Non-Alcoholic Steatohepatitis treatment. (March 2023) - Martini, A.; Villano, G.; Novo, E.; Turato, C.; Quarta, S.; Ruvoletto, M.; Biasiolo, A.; Protopapa, F.; Chinellato, M.; Trevellin, E.; Granzotto, M.; Cannito, S.; et al.
Abstract : Introduction : The liver has a key role in maintaining metabolic homeostasis. The serine protease inhibitor SerpinB3 has been described as critical mediator of liver inflammation and fibrosis. 1-Piperidine Propionic Acid (1-PPA) has been recently proposed as a specific SerpinB3 inhibitor. Aim : To assess a targeted therapeutic strategy for NASH, using 1-PPA in in vitro and in vivo models of NASH. Methods : SerpinB3-transgenic (TG) and SerpinB3-KO mice were fed on MCD and CDAA diets to induce experimental NASH. Starting from the second month, mice were injected with 1-PPA (70 ng/g) and at sacrifice liver specimens were analyzed for histological parameters and for molecular and protein gene expression. Fibrosis and inflammation genes were assessed in LX2 and THP1 cell lines, exposed to human SerpinB3 (100ng/ml) alone or with 1-PPA (100ng/ml) after 24 hours incubation. The expression of CCAAT Enhancer Binding Protein Beta (CEPB-b), a SerpinB3 transcriptor factor, also involved in metabolic disturbances and inflammatory response, was assessed in different cell lines with or without 1-PPA and in mouse livers in relation to SerpinB3 expression. Results : SerpinB3-KO mice showed significantly lower steatosis, inflammation and fibrosis after both dietary regimens, while opposite findings were observed in SerpinB3-TG mice, where treatment with 1-PPA reverted these features. This effect was associated to a parallel reduction of genes involved in adipogenesis, inflammation and fibrosis. These findings were confirmed in LX2 or THP1 cells exposed to SerpinB3. At mechanistic level C/EBP-β induced SerpinB3 and was in turn induced by this serpin, generating a positive loop. 1-PPA was able to inhibit the C/EBP-β - SerpinB3 axis. Conclusions : SerpinB3 - C/EBP-b axis could be relevant in the development of NASH and the SerpinB3 inhibitor 1-PPA is effective in the control of adipogenesis, inflammation and fibrosis in vitro and in NASH models, supporting this approach for a targeted therapy of NASH.